2004
DOI: 10.1007/s00417-004-1053-1
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence tomography can measure axonal loss in patients with ethambutol-induced optic neuropathy

Abstract: The OCT results in these patients with EMB-induced optic neuropathy show considerable loss especially of the temporal fibers. This is consistent with prior histopathological studies that show predominant loss of parvo-cellular axons (or small-caliber axons) within the papillo-macular bundle in toxic or hereditary optic neuropathies. OCT can be a valuable tool in the quantitative analysis of optic neuropathies. Additionally, in terms of management of EMB-induced optic neuropathy, it is important to properly man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
45
0
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(55 citation statements)
references
References 26 publications
(37 reference statements)
6
45
0
4
Order By: Relevance
“…The loss of small caliber axons observed in Tag-1 Ϫ/Ϫ mice is a common feature in various types of metabolic optic neuropathies in humans, where degeneration of the optic nerve takes place (Saadati et al, 1998;Carelli et al, 2002;Zoumalan et al, 2005). The small caliber axons in the optic nerve fire at rapid rates and are thinly myelinated.…”
Section: Discussionmentioning
confidence: 99%
“…The loss of small caliber axons observed in Tag-1 Ϫ/Ϫ mice is a common feature in various types of metabolic optic neuropathies in humans, where degeneration of the optic nerve takes place (Saadati et al, 1998;Carelli et al, 2002;Zoumalan et al, 2005). The small caliber axons in the optic nerve fire at rapid rates and are thinly myelinated.…”
Section: Discussionmentioning
confidence: 99%
“…Studies using optical coherence tomography have also shown that ethambutol therapy is associated with reduction in the retinal nerve fibre layer thickness, suggestive of retinal ganglion cell loss. 21,22 On the basis of these evidence, it is likely that ethambutol not only affects the optic nerve but also causes retinal changes, causing a neuroretinopathy.…”
Section: Discussionmentioning
confidence: 99%
“…1 TAA belongs to the larger class of toxic/nutritional optic neuropathies in which the primary insult is to the mitochondria that disrupts the process of oxidative phosphorylation resulting in axonal loss, preferentially in the fast-firing, parvocellular neurons within the papillomacular bundle. [1][2][3][4] Increased RNFL thickness has been reported in TAA and may occur because of axonal swelling and intraretinal fluid accumulation in the acute phase of visual loss. 4 following cessation of toxic insult and vitamin B12 supplementation correlated with improvement in visual function.…”
Section: Commentmentioning
confidence: 99%
“…Clefts typically occur after trauma or intraocular surgery and may be complicated by a shallow anterior chamber, hypotony, and maculopathy. 1 Slit-lamp-adapted optical coherence tomography (SL-OCT) is a light-based, noninvasive non-contact method of obtaining cross-sectional images of the anterior segment that provides rapid and objective information on the anterior segment dimensions and angle configuration. 2,3 We used SL-OCT (1310-nm diode laser, optical axial image resolution o25 mm, and lateral resolution of 20-100 mm; Heidelberg Engineering GmbH, Dossenheim, Germany) to detect a cyclodialysis cleft, and accompanying ciliochoroidal effusion after blunt trauma in an 8-year-old child.…”
mentioning
confidence: 99%